Parkinsonics: A Randomized, Blinded, Cross-Over Trial of Group Singing for Motor and Nonmotor Symptoms in Idiopathic Parkinson Disease. (20th September 2022) - Butala, Ankur; Li, Kevin; Swaminathan, Aathman; Dunlop, Susan; Salnikova, Yekaterina; Ficek, Bronte; Portnoff, Brandon; Harper, Michael; Vernon, Bailey; Turk, Bela; Mari, Zoltan; Pantelyat, Alexander
Abstract : Introduction. Parkinson's disease (PD) frequently causes communication difficulties due to various voice impairments and there are few treatment options for vocal/communication complaints. We assessed the effects of weekly group singing on PD patients' objective vocal and motoric function, cognition, mood, self-efficacy, and quality of life. Methods. Thirty-two participants were randomly assigned to either a singing group or a facilitated discussion group weekly over 12 weeks. After 12 weeks, participants crossed over for an additional 12 weeks. Evaluations were performed at baseline and every six weeks for 30 weeks. Objective voice measures included volume/loudness (decibels), held vowel duration, jitter, shimmer, and harmonic-to-noise ratio. Additional outcome measures included patient-centered quality of life, voice-related quality of life, MDS-UPDRS, Montreal Cognitive Assessment, and questionnaires assessing depression, self-efficacy, and overall well-being. Results. Twenty-six participants (16 M/10F; Hoehn & Yahr stage 2.3 (range 2–3); and age 68.6 (55–89)) completed the study. Across participants in both groups (intention-to-treat analyses), there was significant improvement from baseline in average loudness on the Cookie Theft picture description at 24 weeks (end of interventions), corresponding with improved minimal reading volumes at 24 weeks and 30 weeks (end of study). Similarly, there were improvements in minimal loudness on Rainbow passage reading at 24 and 30 weeks. There were improvements observed in the Emotional Well-Being (mean delta −12.7 points, p = 0.037 ) and Body Discomfort (mean delta −18.6 points, p = 0.001 ) domains of the PDQ-39 from baseline to week 24 in the overall cohort and greater improvement in the Communication domain for Group S than Group D after 12 weeks of singing (delta −12.9 points, p = 0.016 ). Baseline differences between the participant groups (age, gender, Hoehn & Yahr stage, and several voice loudness measures) and observed improvements during the weekly discussion group period limited our ability to attribute all of the above results specifically to singing (per-protocol analyses). No significant changes in other assessed outcome measures were found. Conclusions. Weekly group singing may improve some aspects of conversational voice volume and quality of life in PD. Some improvements were sustained at least six weeks after interventions ended. Further investigations of the mechanism of benefit and randomized controlled studies (without crossover) to assess the longitudinal effects of singing in PD are necessary.